Government's record on health services - Labour Party (Great Britain). Advisory Committee on Public Health
1927-09 1927 1920s 11 pages -6- Lead Paint It is the white lead contained in paint which adversely affects the health of the painters. This is absorbed, mainly in the form of fine powder and gets into the air, in part from paint dried on the overalls and sheets which painters use, but mainly from the dust produced when a painted surface is sandpapered smooth before a second coat of paint is applied. Although not more than ten to twenty deaths directly attributable to lead poisoning now occur each year among painters in this country, there is a good deal of chronic illness caused by the absorption of lead, and it is well-known that this absorption is an important agent in the causation of degenerative changes of the heart, blood vessels, kidneys and nervous system. Further, lead is one of those poisons the effects of which are sometimes seen even more in the second generation than the first, and it would appear that about double the percentage of children of painters die before birth, than is the case among the population generally. Realising these facts, the Conference of the International Labour Organisation connected with the League of Nations, met in 1921 to enquire what could be done to mitigate these evils. It was pointed out that paints containing no white lead whatever, could be made, and gave nearly, if not quite, as good results, and some representatives were for the complete prohibition of the use of white lead in paints. After much discussion, a compromise was arrived at and a Draft Convention or recommendation prohibiting the use of white lead for the painting of the interior of buildings was carried by the Government, employers, and workers' delegates, of the thirty-two countries represented at the Conference, none opposing and but one abstaining. Every Government that is a member of the International Labour Organisation agrees to submit a draft Convention to its Parliament within eighteen months of its being carried by a two-thirds majority at 292/840/1/15